Thành phần hóa học thân cây dây lóp bóp Gymnosporia stylosa họ dây gối (Celastraceae) - Thu Hà, Nguyễn Thị; Ngân, Trương Bích; Cường, Phạm Văn; Mai Hương, Đoàn Thị; Hùng, Nguyễn Văn; Litaudon, Marc (Vietnam Journal of Chemistry, 2014)
The genus Gymnosporia (Celastraceae) consists of about 300 species in the world. The plants of this genus are rich in triterpenoid, sesquiterpenoid, alkaloid, flavonoid, and phenolic that exhibited a variety of biological and pharmacological activities. The EtOAc extracts of the stems of Gymnosporia stylosa showed cytotoxic activity against cancer human cell line KB (94 % inhibition at 1 mg/mL). In this paper, we report the isolation and structural elucidation of 8 compounds abruslactone A (1), β-amyrin (2), canophyllol (3), 28,29-dihydroxyfriedelan-3-one (4), friedelin (5), syringaldehyde (6), syringic acid (7), and 3,4-dihydroxybenzoic acid (8) from the stems of this plant. It is the first time this plant had researched about chemical constituents in Vietnam as well as in the World. Keywords: Celastraceae, Gymnosporia stylosa, triterpenoid.